Activation of lncRNA lnc-SLC4A1-1 induced by H3K27 acetylation promotes the development of breast cancer via activating CXCL8 and NF-kB pathway - Tongbo Yi; Xiaoqing Zhou; Kai Sang; Xuchen Huang; Jian Zhou; Lan Ge (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
This study aimed to investigate the effect and potential modulation mechanism of lnc-SLC4A1-1 on breast cancer (BC) carcinogenesis. The expression of lnc-SLC4A1-1 in tissue and serum samples from BC patients, as well as BC cell lines, was detected by real-time quantitative reverse transcription-polymerase chain reactions (qRT-PCRs). Next, the expression of lnc-SLC4A1-1 was silenced or upregulated in BC cells, then cell proliferation, apoptosis, migration and invasion were detected using MTT, flow cytometry analysis and Transwell assay. Meanwhile, the expression of apoptosis-related proteins and epithelial-mesenchymal transition-related proteins were detected by western blotting. Furthermore, potential mechanism of lnc-SLC4A1-1 was explored by chromatin immunoprecipitation and RNA immunoprecipitation assays. CXCL8 was overexpressed to evaluate the relationship between lnc-SLC4A1-1 and CXCL8. Lnc-SLC4A1-1 was significantly up-regulated in BC tissue, serum samples and cell lines. In BC cells, lnc-SLC4A1-1 knockdown promoted cell apoptosis and suppressed cell proliferation, migration and invasion. Furthermore, lnc-SLC4A1-1 is transcriptionally activated by H3K27 acetylation, and lnc-SLC4A1-1 interacted with transcription factor (NF)-κB p65, thereby regulating CXCL8 expression. Meanwhile, CXCL8 overexpression partly reversed the effects of lnc-SLC4A1-1 knockdown on cell viability, apoptosis, migration and invasion in BC cells. Lnc-SLC4A1-1 could promote the development of BC by regulating NF-κB/CXCL8.HighlightsLnc-SLC4A1-1 was overexpressed in BC tissues, blood and cell lines.Lnc-SLC4A1-1 was transcriptionally activated by H3K27 acetylation.Lnc-SLC4A1-1 interacted with NF-κB to promote CXCL8 expression.Lnc-SLC4A1-1 could promote the development of BC.